Pengaruh Sanitasi Air Bersih yang Ditinjau dari Keberadaan Fecal Coliform terhadap Kejadian Stunting - Feliyanti; RA. Hoetary Tirta Amallia; RR. Rina Antasari; Delia Yusfarani (Biotropic : The Journal of Tropical Biology, 2024)
Stunting is a global problem that is currently attracting world attention. The future of a nation lies in the quality of the nation's children today and a high incidence of stunting in a country can influence the progress of a nation in the future. Currently, an in-depth study is being carried out on the relationship between environmental sanitation and stunting, apart from lack of food. Therefore, this research aims to correlate the incidence of stunting with the quality of the water used. This research is a cross-sectional study using the quota sampling method. The research results show that there is a significant relationship between coliform numbers in drinking water and the incidence of stunting. Furthermore, a significant relationship was also found between the incidence of diarrhea and the presence of coliforms in drinking water. The results showed that of the 60 samples examined, consisting of 30 samples of water used by the stunted children group and 30 control samples, the coliform number in the WASH for the stunted children group was more than 1,100 CFU/100 mL, while in the non-stunted children group it ranged from 75-120 CFU/100 mL. Similarly, the average coliform count in drinking water consumed by the stunted children group was 4-75 CFU/100 mL, while for children who were not stunted it was 3-4 CFU/100 mL. The results showed a significant association between coliform counts in drinking water and the incidence of stunting, with a p-value of 0.000 which is smaller than alpha 0.05. Furthermore, there was also a significant association between the incidence of diarrhoea and the presence of coliform in drinking water, with a p-value of 0.000 which is smaller than alpha 0.05.